1997
DOI: 10.1080/002072197136075
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of higher testability goals through the modification of shift registers in LFSR-based testing

Abstract: A. AHMAD²The paper is devoted to the achievement of higher testability goals in the BIST environment through the modification of shift registers in LFSR-based testing. The aim is here to take the unified view of the effectiveness of various test-generation and response evaluation techniques with BIST capabilities to justify the design of unified built-in testing scheme. With this objective in mind, a comprehensive analysis of the principles involved has been undertaken to evolve an effective design approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…FSR is one of the most efficient ways to generate pseudorandom sequences. FSR has several applications such as authentication [1], cryptography [2], testing [3], and data compression [4]. FSR has mainly two types: Linear Feedback Shift Register (LFSR) and Non-Linear Feedback Shift Register (NLFSR).…”
Section: Introductionmentioning
confidence: 99%
“…FSR is one of the most efficient ways to generate pseudorandom sequences. FSR has several applications such as authentication [1], cryptography [2], testing [3], and data compression [4]. FSR has mainly two types: Linear Feedback Shift Register (LFSR) and Non-Linear Feedback Shift Register (NLFSR).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the application areas are Built-In Self-Test (BIST) for Very Large Scale Integration (VLSI) circuits' design, cryptography applications like stream ciphers, and error correction and detection codes. In addition, PRBS have been commonly used in the fields of digital signal processing, wireless communications, direct sequence spread spectrum, scrambling &descrambling, encryption & decryption, steganography, and many more (Williams 1984;McCluskey 1985, Bardell et al 1987Nanda et al 1989, Ahmad 1997Jamil and Ahmad 2002;Ahmad 2005aAhmad , 2012Ahmad , 2013aHell and Johansson 2008, Mukherjee et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical relationship, that have been used for estimating the cost of finding a faulty chip, indicates that the cost increases by a factor of 10, as fault finding advances from one level to the next [3] - [7]. However, recent studies have shown that the cost of testing and fault finding, at system and field level, is higher than this factor of 10 and increases exponentially [7] - [9]. Thus, if a fault can be detected at chip or board level, then significantly larger costs per fault can be avoided.…”
Section: Introductionmentioning
confidence: 99%